Analysis of Drought Characteristics in West Java Based on Return Period of Consecutive Dry Days - Amanda Nabila; Sri Nurdiati; I Gusti Putu Purnaba; Mohammad Khoirun Najib (Jambura Geoscience Review, 2026)
Drought is one of the climate change phenomena that must be faced every year in some regions in Indonesia. West Java is a region that often experiences drought in Indonesia. Prolonged droughts are routinely experienced in some areas of West Java, while shorter periods of drought occur between rainfall events in several other regions of West Java. The characteristics of drought in West Java can be analyzed using one of the climate indicators, Consecutive Dry Days (CDD), based on the calculation of the return period of the climate indicator. Therefore, this study aims to analyze the characteristics of drought in West Java based on the calculation of the return period of the parametric distribution function by the CDD. Graph comparison and the Anderson-Darling test were used to estimate the parametric distribution function. Hourly ERA5-Land precipitation (1981–2022) was aggregated to daily totals; annual CDD was defined as the longest run of days with rainfall 1 mm, and return periods were computed using cut-off levels at the 75%, 85%, and 95% quantiles of the regional CDD distribution to map recurrence potential across cities and regencies. Based on the study's results, most of the CDD data in the West Java region have the fittest parametric distribution, namely the inverse Gaussian distribution, followed by the generalized extreme values, Weibull, and lognormal distributions. Further return period analysis shows that the area with the shortest return period to drought so that extreme drought often occurs, is the Indramayu Regency area. In that case, the areas with the longest drought return period are Bogor Regency, Bogor City, and Tasikmalaya City. These findings provide a distribution-based quantification of spatial drought recurrence in West Java to support early-warning and water-resources planning.